Disease Identification in Iris Using Gabor Filter (International Journal of Engineering and Computer Science, 2014)
Biometric features such as facial shape, hand shape, fingerprint, sound and iris have been proposed for human identification. Iris recognition systems are used in world wide applications and more effective   compared with other recent biometric technologies. This paper is mainly concentrated on eye pathology and specifies whether eye disease will cause the iris recognition process to fail. Iris images were taken before and after the treatment of eye disease and the output shows the mathematical difference obtained from treatment. Gabor filter is used to extract the features. This iris recognition was effectively withstood with most ophthalmic disease like corneal oedema, iridotomies and conjunctivitis. This proposed iris recognition should be used to solve the potential problems that could cause in key biometric technology and medical diagnosis.